Composição físico-química da Batata-Doce (Ipomoea batatas) e rendimento na produção de etanol em função da adubação potássica - Silva, Graziella dos Santos Portes (2013)
Ethanol as an alternative source of energy can be produced from various raw materials, the sweet potato has great biomass production to obtain ethanol, associated with hardiness planting. Alcohol from sweet potato is competitive and has a higher yield per ton, besides the possibility of two annual harvests, losing in relation to sugarcane due to productivity. Studies are necessary for improving production processes that influence the synthesis of starch in roots, increasing the conversion to ethanol. The main objective of this study is to evaluate the effect of sources and doses of potassium on the chemical composition of sweet potato roots. The clones of sweet potatoes were identified as UGA118 and UGA119, they were grown in pots in the greenhouse and fertilized with different sources (KCl, KNO3 and K2SO4) and doses (0, 50, 100, 150 and 200 kg ha?¹) potassium as K2O. It was evaluated the following characteristics: fresh mass of leaf and root, dry mass of leaf and root, soluble solids, potassium content in leaves and roots, starch concentration in roots as well as the production of ethanol. The results showed that the clone UGA119 got greater adaptability to the conditions of the experiment, showed higher fresh mass of leaf and root, root dry mass, potassium content in leaf and root as well as higher values of starch concentration and ethanol production. Related to the source, the potassium sulphate stood out as the most promising, generating the highest values of fresh mass of leaf and root, dry mass of leaf and root, soluble solids, starch concentration and ethanol production. However for the characteristics of potassium content on the leaf, the chloride was superior. For the doses applied it was verified the superiority of the results, at the doses between 100 and 150 kg ha?¹ for all the characteristics analyzed. However for the increasing of the desired characteristics, best result was obtained in clone UGA119 when used the source of potassium sulfate at a dose of 150 kg ha?¹ producing 24,781 L ha?¹ of ethanol.